Nonparametric instrumental variables for identification of block-oriented systems - Mzyk, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
A combined, parametric-nonparametric identification algorithm for a special case of NARMAX systems is proposed. The parameters of individual blocks are aggregated in one matrix (including mixed products of parameters). The matrix is estimated by an instrumental variables technique with the instruments generated by a nonparametric kernel method. Finally, the result is decomposed to obtain parameters of the system elements.
Keywords: system identification; instrumental variables; NARMAX system; Hammerstein systems; Wiener system; Lur`e system; nonparametric methods